The girl with the chariot medallion: a well-furnished, Late Iron Age Durotrigian burial from Langton Herring, Dorset. Issue 2 (3rd July 2019) - Russell, Miles; Smith, Martin; Cheetham, Paul; Evans, Damian; Manley, Harry
ABSTRACT: A well-furnished, Late Iron Age Durotrigian burial was found in 2010 by a metal-detectorist at Langton Herring in Dorset. This report examines all aspects of the discovery, paying particular attention to the skeletal remains, a female aged 19–24, providing the most complete, osteobiographical study of an individual buried with a mirror assemblage from the European Iron Age. A combination of artefacts and radiocarbon dating gives a range for the burial of c.AD 25 – cal AD 53. The grave goods themselves are of exceptional interest, representing an accumulation of artefacts acquired from diverse sources, deposited at a time of major cultural and societal change in southern Britain. The results of a geophysical survey are also presented, together with a discussion of additional well-furnished burials in the Durotrigian tribal tradition, which place the burial deposit within a wider social and landscape framework.